Steady-state solution growth of microcrystalline silicon on nanocrystalline seed layers on glass*Project supported by the German Research Foundation (DFG) (No. BO 1129/5-1). (September 2016) - Bansen, R.; Ehlers, C.; Teubner, Th.; Boeck, T.
Abstract: The growth of polycrystalline silicon layers on glass from tin solutions at low temperatures is presented. This approach is based on the steady-state solution growth of Si crystallites on nanocrystalline seed layers, which are prepared in a preceding process step. Scanning electron microscopy and atomic force microscopy investigations reveal details about the seed layer surfaces, which consist of small hillocks, as well as about Sn inclusions and gaps along the glass substrate after solution growth. The successful growth of continuous microcrystalline Si layers with grain sizes up to several ten micrometers shows the feasibility of the process and makes it interesting for photovoltaics.